Examining the challenges of tertiary teaching and learning in the accounting discipline within KwaZulu-Natal South Africa - Makhathini, Lungani; Adam, Jamila; Akpa-Inyang, Francis (Research in Social Sciences and Technology- OpenED Network, 2024)
Financial accounting poses significant challenges for students at tertiary institutions, often resulting in failure, extended graduation timelines, or dropouts, particularly in their first year of study. This study aimed to identify the obstacles encountered in teaching and learning accounting education within South African universities. The research, which employed a qualitative approach, focused on understanding the challenges faced by students in mastering financial accounting at the university level and the underlying causes. Twenty accounting learners from four public tertiary institutions in KwaZulu-Natal were interviewed using open-ended, structured questions via MS Teams. Results highlighted several key themes, including the transition from high school to university, learning strategies and the influence of high school accounting. Challenges identified encompassed the difficult nature of the subject, a shortage of qualified accounting educators, insufficient support staff, poor infrastructure conditions, inadequate classroom facilities and the absence of practical training environments. This study contributes to financial accounting higher education in South Africa by introducing a novel methodological approach, utilising a textual collage to represent data. By merging visual and language-based approaches, the collage offers a fresh perspective on educational research in accounting. Moreover, it contributes to the academic literature within the discipline, aiming to mitigate student dropout rates and prolonged graduation timelines in accounting programmes. Overall, this research endeavours to enhance pedagogical practices and support mechanisms within accounting education, fostering a conducive learning environment for students.